2008
DOI: 10.1007/s11240-008-9473-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth regulators on microspore embryogenesis in coconut anthers

Abstract: The effect of growth regulators on induction of androgenesis in coconut was investigated using seven different growth regulators at various concentrations and combinations. Three auxins (1-naphthalene acetic acid-NAA, indoleacetic acid-IAA, picloram) and three cytokinins (2-isopentyl adenine-2-iP, kinetin, zeatin) were tested either alone or in combination with 2,4-dichlorophenoxyacetic acid (2,4-D), using modified Eeuwens Y3 liquid medium as the basal medium. Among the tested auxins, 100 lM NAA in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 35 publications
1
38
0
6
Order By: Relevance
“…However, in a more recent series of studies it has been reported that somatic embryo structures, with root and shoot apices, have been produced through anther culture (Perera et al 2007a(Perera et al , 2008a, and finally homozygotic plants (Perera et al 2008b). The basic procedures now used employ a culture medium developed by Karunaratne and Periyapperuma (1989) and supplemented with a high concentration of sucrose (9 %) (Perera et al 2008a(Perera et al , 2009c. The addition of activated charcoal (0.1 %) is also important to reduce callus necrosis.…”
Section: Homozygote Production Via Anther Culturementioning
confidence: 99%
“…However, in a more recent series of studies it has been reported that somatic embryo structures, with root and shoot apices, have been produced through anther culture (Perera et al 2007a(Perera et al , 2008a, and finally homozygotic plants (Perera et al 2008b). The basic procedures now used employ a culture medium developed by Karunaratne and Periyapperuma (1989) and supplemented with a high concentration of sucrose (9 %) (Perera et al 2008a(Perera et al , 2009c. The addition of activated charcoal (0.1 %) is also important to reduce callus necrosis.…”
Section: Homozygote Production Via Anther Culturementioning
confidence: 99%
“…A total of 83 plantlets were produced from 32 cultured ovaries (Perera et al 2009a). Tall coconut palm is an allogamous and variable species, is highly heterozygous which a major constraint in conventional breeding (Perera et al 2009b). For the first time, that there is a feasibility of developing homozygous lines in coconut via anther culture.…”
Section: (B) Molecular Detection and Diagnosis Of Diseasesmentioning
confidence: 99%
“…In some reports of coconut the GA 3 is added into the culture medium to promote the germination of somatic embryos (Perera et al, 2009). However the effect of addition of this phytohormome had not been tested on the formation of somatic embryos.…”
Section: Gibberellic Acidmentioning
confidence: 99%